2022
DOI: 10.1039/d1cy02188e
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights for electrochemical reduction of CO2 into hydrocarbon fuels over O-terminated MXenes

Abstract: Two-dimensional (2D) transition metal carbides/nitrides (MXenes) has attracted intensive attention in electrochemical reduction of CO2 into renewable fuels and chemical feedstock. Although encouraging progress has been made so far, but...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 89 publications
0
16
0
Order By: Relevance
“…MXenes, unique accordion-like structures exfoliated from MAX phases (M = transition metal; A = p-block element; X = C and/or N), have recently attracted signicant attention for electronic device, [16][17][18][19] electromagnetic shielding, 20 electrocatalysis, [21][22][23][24] and energy storage and conversion [25][26][27][28][29][30] applications. In particular, the long-term structural stability in acidic electrolytes, 31 large active surface area (21 m 2 g −1 ) 32 and high electrical conductivity (4600 ± 1100 S cm −1 ) 33 make them suitable candidates for HER catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…MXenes, unique accordion-like structures exfoliated from MAX phases (M = transition metal; A = p-block element; X = C and/or N), have recently attracted signicant attention for electronic device, [16][17][18][19] electromagnetic shielding, 20 electrocatalysis, [21][22][23][24] and energy storage and conversion [25][26][27][28][29][30] applications. In particular, the long-term structural stability in acidic electrolytes, 31 large active surface area (21 m 2 g −1 ) 32 and high electrical conductivity (4600 ± 1100 S cm −1 ) 33 make them suitable candidates for HER catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, molecular receptors of chemosensors and chemodosimeters based on the o-hydroxyaniline (OHA) moiety, Phos-1, 3-oxime-4-hydroxy-1,8-naphthalic- n -butylimide (R1)-doped polycaprolactone electrospun fibers, and N -(rhodamine B)-deoxylactam-ethylenediamine were successfully constructed for visual and selective detection of phosgene. However, these techniques require sophisticated procedures, have high maintenance costs, and often are limited by poor portability. ,, On the other hand, nanostructured materials have been extensively investigated in various applications, especially in sensing and catalysis technology because of their facile manufacturing process, high sensitivity and selectivity, capabilities for real-time detection, and simple operations. , The underlying sensing mechanism for these types of devices mainly lies in modulating their conductivity due to the charge transfer between the adsorbates and substrate. The interactions of phosgene on pristine and Sc-doped boron nitride nanotubes (BNNTs) were investigated using quantum mechanical calculations, and researchers found an improved reactivity of phosgene toward Sc-doped BNNTs .…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the high CO 2 RR catalytic performance of Cu/Ti 3 C 2 T x is that it has the inherent catalytic advantages of Cu dopants (large electronic effect, CO* protonation, lower H 2 generation ability) and the inherent physicochemical properties of Ti 3 C 2 T x (rich adsorption sites and defects, high electron density). Parey et al [317] reported that Ti 2 X and Zr 2 X (X = C, N or B) MXenes have good selective conversion ability in catalyzing carbon dioxide reduction reaction (CO 2 RR) to methane (CH 4 ). Using a combination of first-principles calculations and electrocatalysis, all possible pathways for the conversion of carbon dioxide to methane were investigated, and it was found that MXenes tend to carry out CO 2 RR via a more favorable route: CO…”
Section: Mxenesmentioning
confidence: 99%
“…Parey et al. [ 317 ] reported that Ti 2 X and Zr 2 X (X = C, N or B) MXenes have good selective conversion ability in catalyzing carbon dioxide reduction reaction (CO 2 RR) to methane (CH 4 ). Using a combination of first‐principles calculations and electrocatalysis, all possible pathways for the conversion of carbon dioxide to methane were investigated, and it was found that MXenes tend to carry out CO 2 RR via a more favorable route: CO 2 (g)→*COOH→*HCOOH→*CHO→ *H 2 CO→*CH 2 OH→*HOCH 3 →*CH 3 →*CH 4 .…”
Section: Research and Development Of 2d Materialsmentioning
confidence: 99%